A survey of X-ray emission from 100 kpc radio jets. Issue Volume 10:Issue S313(2014) (24th March 2015) - Schwartz, D. A.; Marshall, H. L.; Worrall, D. M.; Birkinshaw, M.; Perlman, E.; Lovell, J. E. J.; Jauncey, D.; Murphy, D.; Gelbord, J.; Godfrey, L.; Bicknell, G.
Abstract: We have completed a Chandra snapshot survey of 54 radio jets that are extended on arcsec scales. These are associated with flat spectrum radio quasars spanning a redshift range z=0.3 to 2.1. X-ray emission is detected from the jet of approximately 60% of the sample objects. We assume minimum energy and apply conditions consistent with the original Felten-Morrison calculations in order to estimate the Lorentz factors and the apparent Doppler factors. This allows estimates of the enthalpy fluxes, which turn out to be comparable to the radiative luminosities.